TEKNIK KONSELING UNTUK MENGATASI POST POWER SYNDROM (SINDROM PURNA KUASA) - Mahmudah, Ummi (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
This study aims to: (1) find out the relationship of work with retirement or retirement, (2) know how to prepare for retirement or retirement, (3) know the counselor's strategy in dealing with post power syndrome. This study uses a literature review method with steps; editing, organizing, and research findings, which are analyzed using deductive methods. This study produced findings: (1) a post power syndrome sufferer needs to be reminded that the employment relationship with retirement includes: work that has been carried out and implemented must have a full or retirement period that will arrive when the position or rank will be released at the time determined, working in the Islamic view is not solely referring to seeking sustenance to support themselves and the family but work includes all forms of practice which have an element of worship carrying out the commands of Allah SWT. (2) How to prepare for retirement or full time include: dilating the heart, accepting sincerely, and being aware of the nature of work or the meaning of real work, being positive and optimistic, arranging activities and activities when retirement comes. (3) The counselor's strategy in overcoming post power syndrome includes: mental health therapy, conducting Islamic counseling, and asking for the help of the closest family to support and pay attention to the sufferer